Utilizing immunostimulants and probiotics for enhancing vannamei shrimp (Litopenaeus vannamei) aquaculture activities - Syifania Hanifah Samara; Gunanti Mahasri; Rahayu Kusdarwati; Dheani Nur Ahadya Syifa Chaerunissa; Anggun Khoirun Nikmah; Elisabeth Benita Indarmastuti (University of Merdeka Malang, 2023)
Vannamei shrimp is one of the important fisheries commodities in Indonesia. This is because vannamei shrimp are expensive, popularly consumed by people around the world, and can be cultured. However, vannamei aquaculture activities are still hampered by disease, less production, and lack of technology implementation. Kedung Pandan Village (Jabon, Sidoarjo, East Java) is one of the potential areas for v vannamei shrimp aquaculture which is also constrained by this issues, so many farmers have gone out of business. This community service activity aims to increase the productivity of vannamei shrimp cultivation by administering immunostimulants and probiotics. In its implementation, this community service activity collaborates with